RELATIONS ENTRE DISCIPLINES SCOLAIRES ET « ÉDUCATIONS À » : PROPOSITION D’UN CADRE D’ANALYSE - Lebrun, Johanne; Roy, Patrick; Bousadra, Fatima; Franc, Serge (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2020)
Ce texte pose les bases conceptuelles d’un cadre d’analyse des relations entre les disciplines scolaires, notamment celles des sciences de la nature et des sciences humaines, et les « Éducations à », afin de mener des analyses comparatives de curriculums dans le monde francophone. Le texte évoque d’abord les principales caractéristiques des « Éducations à » pour ensuite circonscrire les zones de tensions qui découlent de leur prise en charge par les disciplines scolaires. L’assise conceptuelle présentée subséquemment conduit à dégager quatre configurations théoriques pouvant soutenir l’analyse des relations entre les disciplines scolaires et les « Éducations à » sur le plan des finalités éducatives, des apprentissages visés, du statut du savoir disciplinaire et des dispositifs de formation privilégiés. RELATIONSHIP BETWEEN SCHOOL DISCIPLINES AND “ÉDUCATIONS À”: PROPOSAL OF AN ANALYSIS FRAMEWORK This text lays the conceptual foundations for a framework to analyse the relationships between school disciplines, particularly those in the natural sciences and the humanities, and “Éducations à” in order to conduct comparative analyses of curricula in the French-speaking world. The text first discusses the main characteristics of “Éducations à” and then circumscribes the areas of tension that arise from their handling by school disciplines. The conceptual basis presented subsequently leads to the identification of four theoretical configurations that can support the analysis of the relationships between school disciplines and “Éducations à” in terms of the educational purposes, targeted learning, status of disciplinary knowledge, and preferred modes of instruction.